Microalgae and microbial inoculant as partial substitutes for chemical fertilizer enhance Polygala tenuifolia yield and quality by improving soil microorganisms - Su, Yuying; Ren, Ying; Wang, Gang; Li, Jinfeng; Zhang, Hui; Yang, Yumeng; Pang, Xiaohui; Han, Jianping (Frontiers in Plant Science, 2025)
Excessive utilization of chemical fertilizers degrades the quality of medicinal plants and soil. Bio-organic fertilizers (BOFs) including microbial inoculants and microalgae have garnered considerable attention as potential substitutes for chemical fertilizer to enhance yield. In this study, a field experiment was conducted to investigate the effects of BOF partially substituting chemical fertilizer on the growth and quality of medicinal plant Polygala tenuifolia. The growth parameters, bioactive component contents, soil properties and composition of rhizosphere microorganisms were measured. The results indicated that substituting 40% of chemical fertilizer with microalgae showed the most pronounced growth-promoting effect, leading to a 29.30% increase in underground biomass and a 19.72% increase in 3,6’-disinapoylsucrose (DISS) content. Substituting 20% of chemical fertilizer with microalgae improved soil quality, significantly increasing soil organic matter content by 15.68% (p<0.05). Microalgae addition significantly affected the rhizosphere bacterial community composition of P. tenuifolia, reducing the relative abundance of Cladosporium by 33.33% and 57.93%, while increasing the relative abundance of Chloroflexi by 31.06% and 38.27%, under 20% and 40% chemical fertilizer reduction, respectively. The relative abundance of Chloroflexi positively correlated with both the underground biomass and DISS content (p<0.05), indicating that microalgae may stimulate Chloroflexi species associated with carbon cycling, thereby enhancing soil fertility, nutrient absorption, and ultimately leading to increased biomass accumulation and production of bioactive components in P. tenuifolia. In addition, there was no significant difference in underground growth and bioactive component contents between reduced chemical fertilizer dosage combined with solid microbial inoculant (SMI) and polyglutamic microbial inoculant (PMI), compared with 100% chemical fertilizer. Correlation analysis revealed that PMI could increase soil phosphorus availability through Streptomyces recruitment. In conclusion, our findings demonstrated that bio-organic fertilizers can partially substitute chemical fertilizer to improve soil properties and microorganisms, enhancing the growth and quality of P. tenuifolia. This provides a theoretical basis for increasing medicinal plant productivity under chemical fertilizer reduction.